2021
DOI: 10.1186/s12890-020-01380-8
|View full text |Cite
|
Sign up to set email alerts
|

A predictive tool for the assessment of right ventricular dysfunction in non-high-risk patients with acute pulmonary embolism

Abstract: Background Rapid and accurate identification of right ventricular (RV) dysfunction is essential for decreasing mortality associated with acute pulmonary embolism (PE), particularly for non-high-risk patients without hypotension on admission. This study aimed to develop a rapid and accurate tool for predicting the risk of RV dysfunction in non-high-risk patients with acute PE. Methods The medical records of non-high-risk patients with acute PE admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Based on the results of the models from Tables 3 and 4 and literature showing an association between RV dysfunction and PE in the general population, 29 , 30 a final model was created. Since there were only 23 PE events, the final model was limited to 3 predictors to reduce the risk of overfitting the data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the models from Tables 3 and 4 and literature showing an association between RV dysfunction and PE in the general population, 29 , 30 a final model was created. Since there were only 23 PE events, the final model was limited to 3 predictors to reduce the risk of overfitting the data.…”
Section: Resultsmentioning
confidence: 99%
“…A model with D‐dimer>5 mg/L, RV dysfunction, and troponin levels gave the highest predictive discrimination for predicting PE. Although several studies in non‐COVID patients have shown an association between RV dysfunction and PE, 29 , 30 in patients with COVID‐19 it appears that the association is not as straightforward and other variables including troponin levels improve the predictive value of D‐dimer and RV dysfunction for PE significantly. Furthermore, an advantage of this approach is that it may help in better resource allocation for chest CT angiography and limit unnecessary exposure to radiation and contrast use, especially in countries with limited resources.…”
Section: Discussionmentioning
confidence: 98%
“…RV diameter > 30 mm [23][24][25] . To evaluate clinical prognosis, we recorded the presence of shock (de ned as requiring vasopressors) at emergency-department presentation or during the course of hospitalization, 30-and 90-day mortality, and the leading cause of mortality.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 201 patients were included in the nal analysis after the following exclusion criteria had been applied: (1) no CT angiography for PE (i.e., they either had a CT scan that did not follow the pulmonary artery protocol or they did not have any CT imaging data); (2) no thin-slice (≤ 3 mm) image reconstruction; (3) poor imaging quality; (4) radiologic evidence of chronic PE; (5) no signi cant emboli detected in the CT images; (6) thromboemboli in non-pulmonary vascular locations (e.g., venous emboli or left atrial thrombus); or (7) no echocardiography results. [23][24][25] . To evaluate clinical prognosis, we recorded the presence of shock (de ned as requiring vasopressors) at emergency-department presentation or during the course of hospitalization, 30-and 90-day mortality, and the leading cause of mortality.…”
Section: Methodsmentioning
confidence: 99%
“…NT-proBNP has not been investigated in a conclusive randomized clinical trial focused on natriuretic peptide-guided management in PE. Some authors present data on the utility of combining both fore mentioned biomarkers (with the upper limit of normal for NT-proBNP of 600 pg/mL and troponin I either 0.04 ug/mL or 0.05 ug/mL depending on the assay used) and signs of right ventricular strain in either echocardiography or computed tomography of pulmonary arteries (CTPA) to identify intermediate-high risk patients at risk of death or need for rescue thrombolysis [40][41].…”
Section: Natriuretic Peptidesmentioning
confidence: 99%